2014
DOI: 10.1002/ejic.201301494
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent EuIII Complexes Immobilized on a Vermiculite Clay Surface

Abstract: Vermiculite clays were leached with nitric acid and functionalized with (3‐chloropropyl)trimethoxysilane. The resulting materials were modified with the methylimidazolium (MID) group to yield cationic surfaces. These materials were characterized by infrared spectroscopy, elemental analyses, and specific surface area. Tetrakis(β‐diketonate)europate(III) complexes, [EuL4]– [L = dibenzoylmethane (DBM) and thenoyltrifluoroacetone (TTA)], were immobilized on the vermiculite surface containing the imidazolium cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 53 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…[13,[22][23][24][25][26] Recently, complexes have also been used to modify clay minerals. [27][28][29][30][31][32][33][34] As opposed to zeolites, the cavities of which are typically rigid, guest species are accommodated in interlayer space between two "hard" layers; the interlayer space can to some extent be flexibly adjusted by the accommodated guest species. [27] Currently, increased interest is being focused on artificial nanosized clays such as Laponite, which is a synthetic smectic clay with very similar structure and composition to the natural clay mineral hectorite.…”
Section: Introductionmentioning
confidence: 99%
“…[13,[22][23][24][25][26] Recently, complexes have also been used to modify clay minerals. [27][28][29][30][31][32][33][34] As opposed to zeolites, the cavities of which are typically rigid, guest species are accommodated in interlayer space between two "hard" layers; the interlayer space can to some extent be flexibly adjusted by the accommodated guest species. [27] Currently, increased interest is being focused on artificial nanosized clays such as Laponite, which is a synthetic smectic clay with very similar structure and composition to the natural clay mineral hectorite.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic absorption spectroscopy was performed on a Perkin-Elmer 5100 instrument with an air-acetylene flame after previous digestion of samples with an acidic mixture of HF/HNO 3 and HCl. The silicon and aluminum contents were analyzed gravimetrically after fusion with sodium carbonate, as previously described (Silva et al, 2014). X-ray powder diffraction patterns of random samples were obtained in a Shimadzu XRD-7000 diffractometer at 30 kV and 30 mA with nickel-filtered CuKα (α = 0.154 nm) radiation in the range from 3.0°to 80°for 2θ, at a scan rate of 0.60°s − 1 , step size of 0.03°and counting time 1 s per step.…”
Section: Characterizationsmentioning
confidence: 99%
“…Therefore, acid-activated solids have altered structural properties, and their applications can be improved. Acid-activated vermiculites were applied as precursors for clay-polymer nanocomposites, adsorbents (Hashem et al, 2015), catalysts (Chmielarz et al, 2012), catalytic supports (Jin and Dai, 2012) and luminescent species (Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that the resulting products have high specific surface area and porosity [27,29] and are useful in various applications. They can be used as selective adsorbents for specific contaminants from wastewater [24,[29][30][31], support for luminescent complexes [32], and selective catalysts for NO reduction [27].…”
Section: Introductionmentioning
confidence: 99%